2017
DOI: 10.3354/meps12322
|View full text |Cite
|
Sign up to set email alerts
|

Long-term acoustic monitoring of fish calling provides baseline estimates of reproductive timelines in the May River estuary, southeastern USA

Abstract: Long-term acoustic recorders (black instrument in figure) can be used to estimate spawning timelines and rhythms by detecting fish calls associated with courtship. Design by Tim Devine, USCB Graphics ManagerMar Ecol Prog Ser 581: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] 2017 2015). In the family Sciaenidae, sound-producing fishes include Atlantic croaker Micropogonias undulatus, silver perch Bairdiella chrysoura, black drum Pogonias cromis, spotted seatrout Cynoscion nebulosus, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 88 publications
9
68
2
Order By: Relevance
“…No such correlations to temperature are described at other locations. Instead, Monczak, Berry, Kehrer, and Montie ()and Ricci, Bohnenstiehl, Eggleston, Kellogg, and Lyon () mention seasonal, lunar and daily calling rhythms as well as differences between recording locations (Montie et al., ) (Table ). Amorim, Vasconcellos, Marques, and Almada () observe seasonal patterns of emission of different sound types (croaks, grunt trains, boatwhistles) in Lusitanian toadfish ( Halobatrachus didactylus , Batrachoididae); these patterns are significantly correlated to the temperature in the Tagus estuary, Portugal.…”
Section: Calling Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…No such correlations to temperature are described at other locations. Instead, Monczak, Berry, Kehrer, and Montie ()and Ricci, Bohnenstiehl, Eggleston, Kellogg, and Lyon () mention seasonal, lunar and daily calling rhythms as well as differences between recording locations (Montie et al., ) (Table ). Amorim, Vasconcellos, Marques, and Almada () observe seasonal patterns of emission of different sound types (croaks, grunt trains, boatwhistles) in Lusitanian toadfish ( Halobatrachus didactylus , Batrachoididae); these patterns are significantly correlated to the temperature in the Tagus estuary, Portugal.…”
Section: Calling Activitymentioning
confidence: 99%
“…While many studies revealed a relationship between calling activity/sound characteristics and temperature, several studies failed to report such a relationship (cod—Brawn, ; oyster toadfish—Monczak et al., ; Ricci et al., ; Lusitanian toadfish—Amorim et al., ). A drop in the calling activity of the Lusitanian toadfish in late July despite high temperatures (Figure b) most likely reflects seasonal androgen changes according to the authors (the effects of sex steroids on fish acoustic communication are reviewed in Maruska & Sisneros, ).…”
Section: Sound Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of acoustic signalling by burbot presents the possibility of using passive acoustic monitoring to evaluate the location of spawning habitat and the timing of spawning activity. Passive acoustic monitoring has proven successful for mapping the location and timing of the spawning aggregations of sciaenid fishes, such as red drum ( Sciaenops ocellatus ) and spotted seatrout ( Cynoscion nebulosus ; Lowerre‐Barbieri et al., ; Luczkovich & Sprague, ; Monczak, Berry, Kehrer, & Montie, ; Walters, Lowerre‐Barbieri, Bickford, & Mann, ), as well as gadid fishes, such as Atlantic cod (Nordeide & Kjellsby, ) and haddock (Casaretto, Picciulin, Olsen, & Hawkins, ). The development of a reliable protocol for using passive acoustic monitoring to locate burbot spawning aggregations would provide a useful non‐invasive tool to assess the success of reintroduction efforts as well as surveying the spatial distribution and temporal use patterns of burbot spawning habitat.…”
Section: Introductionmentioning
confidence: 99%